RESEPSI EKSEGESIS DAN RESEPSI FUNGSIONAL PADA HADIS‘’JIBRIĪL’’ DALAM CHANNEL YOUTUBE ADI HIDAYAT OFFICIAL - Mawaddah; Anjaliyatul Luaily; Nur Aini (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
Social media is one of the alternatives for delivering information quickly, and it offers various platforms, including YouTube. Anyone can access these platforms, such as the YouTube channel Adi Hidayat Official. This account contains uploaded Islamic-themed videos with various delivery methods. Among these videos is one titled ”About Iman, Islam, and Iḥsān.”In presenting this theme, Ustadz Adi Hidayat conveys a hadith commonly known as the Hadith of Jibrīl (Gabriel). This research aims to examine how the hadith is presented on the Adi Hidayat Official channel, as well as the exegetical reception and functional reception of the hadith. The study employs a qualitative method with direct observation of the video on the Adi Hidayat Official YouTube channel under the theme ”About Iman, Islam, and Iḥsān” as the primary source. Additionally, a literature review approach is used as a secondary source related to the research topic.The findings indicate that in delivering the hadith, Ustadz Adi Hidayat presents it in his religious lecture (tausiyah) to provide understanding to the audience as an argument or motivation in worship. He emphasizes that **Islam, Iman, and Iḥsān** are closely interconnected and complementary in attaining the pleasure of Allah (swt). The study also explores the exegetical and functional reception of the hadith as presented